Experiences and outcomes of group volunteer befriending with patients with severe mental illness : an exploratory mixed-methods study in Colombia (2021)
Background: Improving care for patients with severe mental illness in Latin America requires effective strategies that are low-cost. One such strategy is a volunteering scheme, referred to as befriending, which seeks to support the social integration of p